2020
DOI: 10.3390/ijms21061956
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Intracranial Major Artery Stenosis/Occlusion According to RNF213 Polymorphisms

Abstract: Intracranial major artery stenosis/occlusion (ICASO) is the major cause of ischemic stroke. Recent studies have suggested that variants of RNF213, a susceptibility gene for moyamoya disease (MMD), are also related to non-MMD ICASO. Regarding the predominant involvement of steno-occlusion on anterior circulation in MMD, we hypothesized that the ICASO distribution pattern (anterior/posterior) in non-MMD may differ according to RNF213 variants. This study analyzed 1024 consecutive Korean subjects without MMD who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The role of the so‐called “Moyamoya disease factor: RNF213” in Asian MA is still unclear. The RNF213 gene encodes a RING finger protein that possesses both ubiquitin ligase activity and ATPases associated with diverse cellular activities [74]. A founder mutation in this gene is mainly found in familial and sporadic patients with MA in Japan and Korea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of the so‐called “Moyamoya disease factor: RNF213” in Asian MA is still unclear. The RNF213 gene encodes a RING finger protein that possesses both ubiquitin ligase activity and ATPases associated with diverse cellular activities [74]. A founder mutation in this gene is mainly found in familial and sporadic patients with MA in Japan and Korea.…”
Section: Discussionmentioning
confidence: 99%
“…A founder mutation in this gene is mainly found in familial and sporadic patients with MA in Japan and Korea. Experimental data suggested multiple pathogenic mechanisms involving endothelial function, smooth muscle cell proliferation, inflammatory signaling pathways, hemostasis, angiogenesis, and vascular remodeling [74–77]. Currently, the exact role of RNF213 in vascular disorders remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies mainly focused on gene polymorphism of the tissue inhibitor of metalloproteinase (TIMP) [ 45 ], the vascular smooth muscle cell (SMC)-specific isoform of alpha-actin (ACTA2) [ 46 ], and ring-finger protein 213 (RNF213) [ 47 , 48 ]. Mutations in RNF213, a zinc ring-finger protein that is related to intracranial major artery stenosis/occlusion [ 49 ], may affect the expression of some micro-RNAs and proteins associated with signaling processes involved in angiogenesis and immune activities that underlie the pathology and progression of MMD [ 50 ]. The amino acid substitution p.R4859K, the first identified RNF213 polymorphism associated with MMD, was found in 95% of patients with familial MMD, 80% of those with sporadic MMD, and 1.8% of control individuals in a Japanese population, in a genome-wide linkage and exome analysis study [ 51 ].…”
Section: Geneticsmentioning
confidence: 99%
“…In 2020, Han et al suggested that platelet activation and renin secretion may help guide clinical management and may further elucidate the pathogenesis of asymptomatic MMA(253). In 2020, Kim et al suggested that additional study of the molecular biology and functioning of RNF213 may further ascertain the pathophysiology of cerebrovascular disease and ICASO(233). In 2020, Wang et al stated that larger cohorts, including different ethnicities, may be warranted to further clarify associations between TGFB1 SNPs and MMA(235).…”
mentioning
confidence: 99%